Conditions for the development of the right to feeding as fundamental right (2015)
This document presents a study of the development of the right to food and the subjects that occupy it , contextualization of social conditions , the concentration of wealth in the world, and the problems existing And existing problems of undernourishment . The relationship between the right to adequate food and the fundamental rights work. Another aspect relates the theoretical and legal elements supporting the DAA , based on subjective rights , inalienable , the metarights , fundamental rights , the concept of vital minimumcommitment involved in customary international law and economic rights It also works on international obligations that have signed Latin American countries and the constitutional and political forms that have to solve this DAA populations , finally it referred to a part of the Colombian situation.